Ultra-high efficiency bremsstrahlung production in the interaction of direct laser-accelerated electrons with high-Z material - Tavana, P.; Bukharskii, N.; Gyrdymov, M.; Spillmann, U.; Zähter, Ş.; Cikhardt, J.; Borisenko, N. G.; Korneev, Ph.; Jacoby, J.; Spielmann, C.; Andreev, N. E.; Günther, M. M.; et al. (Frontiers in Physics, 2023)
High performance of laser-driven sources of radiation is in focus of research aimed at the study of high energy density matter, pair production and neutron generation using kJ PW-laser systems. In this work, we present a highly efficient approach to generate an ultra-high flux, high-energy bremsstrahlung in the interaction of direct laser-accelerated (DLA) electrons with a several-millimeters-thick high-Z converter. A directed beam of direct laser-accelerated electrons with energies up to 100 MeV was produced in the interaction of a sub-ps laser pulse of moderate relativistic intensity with long-scale plasma of near-critical density obtained by irradiation of low-density polymer foam with an ns laser pulse. In the experiment, tantalum isotopes generated via photonuclear reactions with threshold energies above 40 MeV were observed. The Geant4 Monte Carlo code, with the measured electron energy and angular distribution as input parameters, was used to characterize the bremsstrahlung spectrum responsible for the registered yields of isotopes from 180Ta to 175Ta. It is shown that when the direct laser-accelerated electrons interact with a tantalum converter, the directed bremsstrahlung with an average photon energy of 18 MeV and ∼2⋅1011 photons per laser shot in the energy range of giant dipole resonance (GDR) and beyond (≥7.5 MeV) is produced. This results in an ultra-high photon flux of ∼6 × 1022 sr−1·s−1 and a record conversion efficiency of 2% of the focused laser energy into high-energy bremsstrahlung.